2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6854246
|View full text |Cite
|
Sign up to set email alerts
|

Optimality of proper signaling in Gaussian MIMO broadcast channels with shaping constraints

Abstract: Proper (i.e., circularly symmetric) Gaussian signals are known to be capacity-achieving in Gaussian multiple-input multiple-output (MIMO) broadcast channels with proper noise in the sense that the sum rate capacity under a sum power constraint is achievable with proper Gaussian signaling. In this paper, we generalize this statement by proving that the optimality of proper Gaussian signals also holds under a shaping constraint, i.e., a sum covariance constraint instead of a power constraint. Moreover, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However, until recently, it had not been shown that the optimality of proper signals also holds under a shaping constraint, i.e., a constraint on the sum transmit covariance matrix instead of on the sum power. 7 In our recent works [34], [35], we used the minimax duality with linear conic constraints from [56], [57] in combination with a power shaping matrix and an impropriety matrix to show this more general result. As discussed in Section III.D, these matrices fit into the framework proposed in this paper.…”
Section: Optimality Of Proper Signaling In Gaussian Mimo Broadcastmentioning
confidence: 99%
See 2 more Smart Citations
“…However, until recently, it had not been shown that the optimality of proper signals also holds under a shaping constraint, i.e., a constraint on the sum transmit covariance matrix instead of on the sum power. 7 In our recent works [34], [35], we used the minimax duality with linear conic constraints from [56], [57] in combination with a power shaping matrix and an impropriety matrix to show this more general result. As discussed in Section III.D, these matrices fit into the framework proposed in this paper.…”
Section: Optimality Of Proper Signaling In Gaussian Mimo Broadcastmentioning
confidence: 99%
“…In order to briefly sketch the key idea of this approach, we reproduce the proof for the special case of a sum rate maximization in a system with two users. The more general weighted sum rate maximization for an arbitrary number of users is studied in [35].…”
Section: Optimality Of Proper Signaling In Gaussian Mimo Broadcastmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results use our minimax duality to proof the optimality of proper signaling for the MIMO broadcast channel under a shaping constraint [26] and for the MIMO relay channel with partial decode-and-forward [34]. A key ingredient for the proof is the observation that in a composite real representation a covariance matrix can be partitioned in a power shaping component and an impropriety component, such that the components are elements of linear subspaces that are orthogonal complements.…”
Section: Optimality Of Proper Signalingmentioning
confidence: 99%
“…The use of the linear conic constraints is not motivated by a specific application, instead we will see that they are general enough to model a large class of constraints, including sum-power constraints, per antenna power constraints, or shaping constraints. Shaping constraints for the optimization of transmit covariances in MIMO systems are for example considered in [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%